Pengaruh ROE dan DER Terhadap Harga Saham pada Perusahaan Food & Beverage yang Terdaftar di BEI - Hasbi Dwi Oktafianto, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of the study is to test and analyze the influence of ROE and DER on the share price of Food & Beverage Companies listed on the IDX in the period 2021 - 2024 both partially and simultaneously. This type of research uses a quantitative approach, namely, the sampling technique using purposive sampling. The data analysis used was panel data regression analysis. Test statistics using Software Eviews. 8 samples were obtained with 32 observations. The results of the study show that ROE has an effect, while DER does not have a significant partial effect on stock prices. Simultaneously, independent variables have an influence and significant effect on the stock price, with a determination coefficient of 0.246197 which means 24.6197%, the stock price can be explained by ROE and DER, while the remaining 75.3803% is explained by other variables that are not studied in this study. The results of this study are useful for investors and managers in choosing stocks that will increase stock prices.